Study On Scouring and Protection of USBR-III Type Downstream of Spillway - Djunur, Lutfi Hair (Universitas Negeri Semarang, 2022)
Abstract. In the downstream part of the spillway building, especially in the flood way, occurs phenomenon of changing flow conditions from super critical to sub critical which causes a hydraulic jump and used by energy absorbers to reduce flow energy. The hydraulic jump in the floodway causes scouring of the bottom, particularly in the unprotected downstream spillway. Using 3 different dimensional baffle block models provides three different discharge variations in four flow simulations. Based on the results of the analysis and planning of the baffle block, it is found that the effectiveness in protecting the downstream scour of the spillway, namely baffle block dimensions of 1:1, 1:3 and 1:5. The three models of baffle blocks are used to determine the change in channel cross-section, scour pattern, scour volume and flow parameters that occur in downstream of spillway. The results showed that without baffle block was 32.80%, 1:1 baffle block was 43, 24%, 1:3 baffle block was 10.01% and 1:5 baffle block was 47.77%. The results of the drainage simulation showed that the higher the water level and the velocity of the flow at the bottom of the channel, the less the flow will be and will not be able to lift the bottom material of the channel